CASL for CafeOBJ Users - Mosses, Peter D. (BRICS Report Series, 2000)
Casl is an expressive language for the algebraic specification of software requirements, design, and architecture. It has been developed by an open collaborative effort called CoFI (Common Framework Initiative for algebraic specification and development). Casl combines the best features of many previous main-stream algebraic specification languages, and it should provide a focus for future research and development in the use of algebraic techniques, as well facilitating interoperability of existing and future tools. This paper presents Casl for users of the CafeOBJ framework, focusing on the relationship between the two languages. It first considers those constructs of CafeOBJ that have direct counterparts in Casl, and then (briefly) those that do not. It also motivates various Casl constructs that are not provided by CafeOBJ. Finally, it gives a concise overview of Casl, and illustrates how some CafeOBJ specifications may be expressed in Casl.